Thanks this came in handy bc I'm a beginner
(0,-3) (1, -1) (2, 1) ....
Answer:
For instance, if the point (1, 3) is on the graph of the function, then the point (3, 1) is on the graph of the inverse. That is, if you start with x = 1, you will go to y = 3; then you plug this into the inverse, and you'll go right back to x = 1, where you started from.
Answer:
1443.36
Step-by-step explanation:
6014*.24=1443.36
Hope it helps
Is this even answerable, because u would need to figure out what ‘b’ is to figure out the answer